What Level Should Preoperative Albumin of Thoracic and Lumbar Tuberculosis Patients Be Reached: A Case-Controlled Study - Jiang, Guanyin; Zhu, Yong; Luo, Wei; Zhang, Wei; Qin, Wanyuan; Ou, Yunsheng (Frontiers in Nutrition, 2022)
Objective: To explore the risk factors of thoracic and lumbar tuberculosis patients’ hypoalbuminemia and develop a scoring scale, according to which the thoracic and lumbar tuberculosis patients were divided into 2 groups to respectively calculate the perioperative albumin changes, so as to find out the preoperative albumin recommended value. Methods: A total of 166 thoracic and lumbar tuberculosis patients who underwent spinal focus debridement between January 2012 to May 2020 were identified into 2 groups with and without postoperative hypoalbuminemia (n=131 and n=35, respectively). Recording and analyzing clinical characteristics by multivariate analysis to establish a scoring scale. Using this scale, spinal tuberculosis patients were divided into high-risk group and low-risk group, and then calculated the average decrease of postoperative albumin in both group. Combined with the diagnostic threshold of hypoalbuminemia, we proposed the preoperative albumin safe values of the thoracic and lumbar tuberculosis patients. Results: 131 of 166 patients experienced postoperative hypoalbuminemia after spinal focus debridement. Multivariate binary logistic regression analysis identified pulmonary tuberculosis (adjusted odds ratio=0.270, p=0.012), preoperative serum albumin value (adjusted odds ratio=0.754, p<0.001) and operation time (adjusted odds ratio=1.017, p=0.002) as independent risk factors for the occurrence of postoperative hypoalbuminemia in thoracic and lumbar tuberculosis patients. According to the OR value the risk factors are assigned to make the scoring scale, ROC curve indicates that postoperative hypoalbuminemia rises when the score is greater than or equal to 4 points. The scoring scale is tested in derivation set (166 patients) showed: the sensitivity-51.9%, the specificity-91.4% and in validation set (102 patients) showed: the sensitivity-63.6%, the specificity-86.1%. The perioperative albumin decreased value is 4.71±2.66g/L in low-risk group and 8.99±3.37g/L in high-risk group (p<0.001). Conclusion: Complicated with pulmonary tuberculosis, low preoperative albumin value and long operation time can lead to postoperative hypoalbuminemia in spinal tuberculosis patients. The scoring scale can effectively assist physician to evaluate whether thoracic and lumbar tuberculosis patients develop hypoalbuminemia after surgery. The scale is simple and reliable, and has clinical guiding significance. For low-risk patients and high-risk patients, preoperative albumin value should reach to 40g/L and 44g/L, respectively, so as to effectively avoid postoperative hypoalbuminemia.